Educative Prohibition and Guided Freedom in Islamic Education: A Comparative Study of QS. Luqman 13 and Child-Centered Education - Mohamat Harianton; Bagus Jamroji (PT. Caesarindo Triloka Persada, 2026)
This study examines the pedagogical meaning of prohibition in QS. Luqman 13 and its relevance to contemporary child-centered education. The study is motivated by the tension between modern educational paradigms that emphasize freedom, autonomy, and self-expression, and the need for moral boundaries in children’s character formation. Using a qualitative library research design, this study applies thematic Qur’anic interpretation and comparative educational analysis. Primary sources include QS. Luqman 13 and classical Qur’anic commentaries, while secondary sources include works on Islamic education, character education, and modern educational theories. The findings show that the prohibition expressed in the phrase lā tushrik billāh is not merely a normative command, but an educative boundary delivered through affection, dialogue, and rational moral reasoning. The phrase yā bunayya reflects a compassionate pedagogical relationship, while the explanation that shirk is a great injustice provides a rational foundation for moral internalization. Compared with child-centered education, Qur’anic pedagogy offers a model of guided freedom that balances autonomy with value-based boundaries. This study contributes to Islamic education scholarship by reconstructing prohibition as a humanistic, dialogical, and transformative pedagogical instrument. The study concludes that contemporary education should not eliminate prohibition, but should reinterpret it as an educative boundary that supports self-control, moral awareness, and responsible freedom.